Factors Influencing the Adoption of Artificial Intelligence (AI) in Recruitment process : A Study of Medium-Sized Firm(s) in Ho Chi Minh city, Vietnam - Nguyen, Ngoc Thuy Vy; Hořáková, Marie; Legnerová, Kateřina, 1965-; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2025)
The aim of this thesis is to explore key factors influencing the adoption of Artificial Intelligence (AI) in the recruitment process within the scope of medium enterprises in Ho Chi Minh city, Vietnam. With the rise of AI globally, understanding barriers and drivers of its implementation to human resources field in particular and the economy in Vietnam in general is critical. This study aims to identify what organizational, technical, and external impact facilitate or limit the adoption of artificial intelligence in recruitment, while also examining the role of cultural and regulatory contexts unique to Vietnam. Through qualitative research method, the research seeks to give actionable insights for medium-sized firms in Ho Chi Minh city to effectively integrate AI into their recruitment processes, and to contribute to the wider academic discourse of AI adoption in emerging economies. Lastly, the findings will offers practical recommendations to help medium-sized firms in Vietnam improve their recruitment efficiency and competitiveness through the strategic use of AI technologies.
Vedoucí práce: Marie Hořáková
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: bachelor of business administration [obor bakal. práce]; bakalářské práce; bachelor's theses